PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA NEGERI 10 BEKASI - Hendri; Irfan Mahendra (Jurnal Sistem Informasi, 2014)
Abstract— Academic information system is a web -based system that provides information about the school's academic . SMA Negeri 10 Bekasi is one of the schools that do not have a computerized information system , so as to obtain the information of parents , students , and the community must come to school. Schools that do not have this information system is considered very requires web-based academic information system in order to provide convenience to parents , students and the public in obtaining information . Software development method used is the Waterfall method. With web-based academic information system is expected to help resolve the problems . Parents and students do not need to come directly to the school to seek and obtain the required information . Thus helping to provide information quickly and accurately.